Designing for health and well-being: Implementing Human Centered Design principles into an existing workplace precinct through adaptive re-use practices - Malherbe, Henk (School of Architecture, Planning and Geomatics, 2024)
This paper aims to investigate the role of architectural interventions in promoting humancentered design principles and creating healthier buildings. With more than half of the global population now residing in urban areas and sedentary lifestyles becoming prevalent, there has been a global surge in chronic diseases and mental well-being decline as a result of lack of movement and stimulus to nature. Through understanding the historical significance of design strategies which played a part in shaping this behavior, this paper will critically analyze existing research to identify comprehensive interventions that can address contemporary health challenges, specifically lack of physical movement and access to nature. To contextualize the research, a historical analysis will explore how environmental design and architecture played a crucial role in restricting our movement patterns, and segregating our communities. The built environment, at its core, holds immense sway over human health and physical activity. It encompasses vital factors such as air quality, natural light, and our general state of well-being.